Board attributes, financial distress and fruitless and wasteful expenditure in south african state-owned enterprises - Thusini, Philani (College of Accounting, 2025)
Purpose: Poor financial viability, perpetual inefficiencies and wastage are some of the challenges facing South African state-owned enterprises (SOEs). SOE boards are often criticised for failing to protect the financial sustainability of these entities and prevent the incurrence of fruitless and wasteful expenditure. Therefore, this study seeks to investigate the relationship between board attributes and financial distress and the relationship between board attributes and fruitless and wasteful expenditure in South African SOEs. Methodology and research design: The study adopted a quantitative approach and used ordinary least squares regression on a sample of 27 South African SOEs over a five-year study period from 2016 to 2020. Five board attributes, being: board size, board activity, board tenure, board gender diversity, and board education, were selected as the independent variables of the study. SOE size and audit opinion were identified as the control variables. Findings: The study results indicate that board size and board gender diversity have a negative and significant relationship with financial distress. However, a direct and statistically significant relationship was found between board education and financial distress. No statistically significant relationship was found between the study board attributes and fruitless and wasteful expenditure. Research implications: The findings provide policymakers with insight on the board attributes that influence financial distress and fruitless and wasteful expenditure in SOEs. Originality/value: Whilst there is a plethora of studies on board governance, many of these prior studies have focused on private sector companies. This study is, therefore, useful in understanding board attributes that affect financial distress and fruitless and wasteful expenditure in the context of South African SOEs. Moreover, we are not aware of any prior study that has empirically tested the relationship between board attributes and fruitless and wasteful expenditure.